2007
DOI: 10.1016/j.juro.2006.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Lymph Node Dissection for Penile Carcinoma: Extent of Inguinal Lymph Node Involvement as an Indicator for Pelvic Lymph Node Involvement and Survival

Abstract: Patients with only 1 or 2 inguinal lymph nodes involved without extracapsular growth and no poorly differentiated tumor within these nodes are at low risk of pelvic lymph node involvement and have a good prognosis with a 5-year survival rate of approximately 90%. Pelvic lymph node dissection seems to be unnecessary in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 14 publications
1
96
0
5
Order By: Relevance
“…And so further analysis with large study groups on perineural invasion and nodal disease will be needed in future. 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…And so further analysis with large study groups on perineural invasion and nodal disease will be needed in future. 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…This follows work that has demonstrated that the extent of metastatic disease in the nodes has great prognostic implications. 3,5 Series have shown 5-year mortality rates of roughly 25% for low-volume inguinal metastases and 75% for patients with greater than 2 positive nodes. 3,6 A recent large retrospective review of more than 100 patients undergoing lymphadenectomy for penile cancer demonstrated that disease in more than 2 lymph nodes, extracapsular nodal disease, bilateral node-positive disease and pelvic lymph node metastasis are independent prognostic factors for disease-specific survival.…”
Section: Burden Of Inguinal Diseasementioning
confidence: 99%
“…2,6 In a series by Lont and colleagues, 5 25 of 102 patients (25%) with pathologically proven inguinal metastases were later proven to have pelvic node disease, and 4 of these patients (16%) achieved long-term disease-free survival. Risk factors for the presence of pelvic nodal disease in patients with inguinal node disease included more than 2 positive nodes, extracapsular extension of disease and presence of high-grade cancer in inguinal nodes.…”
Section: Pelvic Lymph Nodesmentioning
confidence: 99%
See 2 more Smart Citations